Elbow injury in an adolescent baseball player - Waugh, A. M.; Hosey, R. G. (Journal of Athletic Training, 2012)
Background: A 12yo baseball player with no history of upper extremity injury presented with a primary complaint of forearm and elbow 7/10 pain after being hit by a pitch. There was no obvious deformity by visual inspection or palpation. He was point tender about the proximal ulna at the site of contact. The athlete had full active and passive ROM of the shoulder, elbow and wrist. However, ROM of the elbow was painful. There was not a report of numbness or pain radiating to the hand. Initial treatment consisted of ice and over the counter analgesics for treatment of swelling and pain, and activity as tolerated. Differential Diagnosis: Contusion, Ulna fracture, UCL Sprain, Epicondylitis Treatment: The athlete was referred to a primary care sports medicine physician 10 days post injury. At that time the athlete reported continued but lessening pain 2/10 that increased with throwing. The physician exam revealed mild swelling about the elbow with pain focused in the forearm. Distal pulses were 2+ and sensation was intact throughout the upper extremity. Flexion, extension, pronation, and supination of the wrist were full and pain free. Elbow ROM was full, however, hyperextension was painful. Varus and Valgus maneuvers did not elicit pain or instability of the elbow at 0°, 30°, or 60°. Plain radiographs of the right elbow were ordered by the physician and revealed an incomplete intra-articular fracture of the olecranon and soft tissue swelling about the posterior elbow. It was determined the fracture was chronic and un-related to the recent trauma. The athlete was diagnosed with a forearm contusion and an olecranon stress fracture, placed in a sling, and withheld from athletic activity. A two week follow-up with repeat radiographs was scheduled with an orthopaedic surgeon. This exam revealed the patient was asymptomatic with full ROM and no pain. Plain radiographs showed the lucency to be less clear with an increase in sclerosis along the margins. The orthopaedic confirmed the assessment of an olecranon stress fracture. At this time the reatment plan was to discontinue use of the sling and to allow the athlete to begin football activity at the 1 month mark in a hinged elbow brace for protection. He was instructed to stop activity if any symptoms returned. In addition, it was recommended that the athlete abstained from pitching/throwing for 3 months and follow-up in 1 month with the primary care sports medicine physician. At the 2 month follow-up exam the follow-up xrays revealed interval healing of the fracture site. In addition, the athlete reported he tolerated football activity and remained asymptomatic. The athlete was released to football activity as tolerated in the brace and refrain from pitching/throwing. The athlete was not planning to participate in baseball through the winter follow-up was scheduled for 2 months. At that time radiographs showed a healed fracture. The athlete was released to play basketball and will be begin a throwing program at 6 months. Uniqueness: An asymptomatic stress fracture was diagnosed due to an unrelated injury in a young adolescent athlete. Due to the incomplete nature of the stress fracture this was able to heal without surgical intervention. Had this not been detected early, the fracture would have likely worsened requiring fixation due to the athlete`s participation in sporting activities. Also as stress reactions and fractures are typically seen in an older population. Conclusion: With the increasing popularity of competitive sports at younger ages, it is important to be aware of stress and overuse injuries in a pediatric population. These stresses to skeletally immature bones can lead to more serious injuries in this population.